(untitled) (World Bulletin of Social Sciences, 2024)
It is necessary to optimize the parameters of artificial irrigation devices considering climatic conditions. In the article, the process of irrigation and the trajectory of movement of the water jet, as well as the influence of variable environmental factors on it, have been investigated. A mathematical model of the water jet movement has been obtained. The mathematical model of the water jet takes into account the distance and time of irrigation, as well as the direction and speed of the wind.